A simple and straightforward mechanochemical synthesis of the far-from-equilibrium zinc aluminate, ZnAl2O4, and its response to thermal treatment. Issue 67 (24th July 2015) - Fabián, Martin; Bottke, Patrick; Girman, Vladimír; Düvel, Andre; Da Silva, Klebson Lucenildo; Wilkening, Martin; Hahn, Horst; Heitjans, Paul; Šepelák, Vladimír
<x xml:space="preserve">Abstract</x> Far-from-equilibrium nanostructured ZnAl2O4 is prepared via simple and straightforward mechanochemical synthesis. Upon heating above 1100 K, mechanosynthesized ZnAl2O4 relaxes towards a structural state that is similar to the bulk one.